1923 N.H. Laws 138 § 9 - (:unkn) unknown (General Publisher, 1923)
Whoever, without being licensed as hereinafter provided, sells, advertises, or exposes for sale, or has in his possession with intent to sell, pistols or revolvers, shall be punished by imprisonment for not more than two years.
--
Keywords: TRANSFER ONLY